Evaluation of Sympathetic Function tests During Different Phases of Menstrual Cycle in Apparently Healthy Young Females – A Cross Sectional Study - Khakurel, Gita; Gautam, Kalyan (Medical Journal of Shree Birendra Hospital, 2025)
Introduction: Menstrual cycle consists of three phases namely menstrual, follicular and luteal phase. It is reported that hormonal fluctuations during different phases may result in some autonomic function alterations. The objective of this study is to evaluate the sympathetic function tests during different phases of menstrual cycle in apparently healthy young females. Methods: A descriptive cross-sectional study was conducted among 100 apparently healthy female students of medical, dental and nursing streams of Kathmandu Medical College for a year. Young girls in the age of 17 - 23 years with regular 28 days menstrual cycles for last six months was included in the study. The sympathetic function tests like blood pressure response to immediate standing, blood pressure response to sustained hand grip exercise and cold pressor test was done. Data was collected and statistical analysis was done. A P value of less than ≤ 0.05 was considered statistically significant. Results: Resting systolic and diastolic blood pressure were increased in luteal phase (119.03 ± 7.04, 88.84 ± 5.88) compared to menstrual (112.07 ± 7.43, 70.44 ± 7.80) and follicular phase (112.91 ± 7.55, 73.36 ± 5.63) of the menstrual cycle. Fall in postural systolic blood pressure (blood pressure response to immediate standing) was statistically significant (P value < 0.05) between follicular (10.61 ± 7.39) and luteal phase (7.39 ± 6.82). Rise in systolic blood pressure in response to cold pressor test showed significant increase in the luteal phase (15.81 ± 7.84) compared to menstrual (12.18 ± 10.38) and follicular phase (11.76 ± 8.54). Blood pressure response to isometric handgrip exercise was statistically significant during the luteal phase compared to the menstrual and follicular phase. Conclusions: The result of the present study concludes that the sympathetic function test responses were highest in the luteal phase of the menstrual